SYNTHESIS OF A NANOCOMPOSITE BASED ON MXENE (TI3C2TX) AND ZNO AS A PHOTOCATALYST FOR THE REDUCTION OF BICARBONATE - Joel Michael Siregar, Jeconiah
The increase in atmospheric carbon dioxide (CO2) due to fossil fuel usage has caused a number of negative impacts, such as climate change and global warming. One solution to this issue that is being developed today is the light-assisted chemical reduction of CO2 (photoreduction) into alternative fuels such as methanol (CH3OH), methane (CH4), and formic acid (HCOOH). This photoreduction process requires an efficient catalyst in the form of a semiconductor. Zinc oxide (ZnO) is a semiconductor that has been used as a photocatalyst for CO2 on account of its low production cost and high photosensitivity. However, the performance of ZnO as a photocatalyst is limited due to its wide band gap energy. In order to overcome this issue, ZnO can be composited with MXenes, a nanomaterial based on transition metal carbides/nitrides. MXenes possess ideal qualities as a co-catalyst, including wide surface area, high mechanical and chemical stability, and an abundance of active sites. Based on these considerations, this research will focus on synthesizing of MXene/ZnO nanocomposites and evaluating its photocatalytic performance using bicarbonate (HCO3–) as an alternative precursor. Products synthesized in this research consist of Ti3C2Tx MXene; ZnO from 4 different precursors, namely Zn(NO3)2 (ZP1), ZnCl2 (ZP2), Zn(CH3COO)2 (ZP3), and ZnSO4 (ZP4); and the MXene/ZnO nanocomposite catalyst (M-ZP). An array of characterizations, consisting of X Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), dan UV-Visible Diffuse Reflectance Spectroscopy (UV-DRS) were carried out to confirm the successful synthesis of the products. After the photoreduction test, it was found that ZP1 had the highest catalytic activity at 197,07 mmol formic acid/gram catalyst, despite not having the lowest band gap energy. This might be caused by the particle size and morphology of ZP1. M-ZP1, the composite between MXene and ZP1, displayed a significant reduction in band gap energy and increase in Urbach tail energy. This is reflected by its enhanced catalytic activity at 228,33 mmol formic acid/gram catalyst. This performance is attributed to the Schottky junction interaction between the MXene and ZnO interface, which limits the recombination of charges on the ZnO surface.